Analytical review on secure communication protocols for 5G and IoT networks. (14th June 2022) - Premalatha, J.; Swamidason, Iwin Thanakumar Joseph; Harshavardhanan, Pon; Anandaraj, S.P.; Jeyakrishnan, V.
Internet of things (IoT) provides an exciting future for the interaction of devices utilising computing and sensorial capabilities. Among the existing technologies, fifth generation (5G) schemes are expected to be the motivating force for the realisation of IoT concept. This research paper reviews existing state-of-art on the secure communication for 5G and IoT networks. We have created a taxonomy and categorised the research works based on the protocols such as light weight authentication protocol, trust-aware routing protocol, service-oriented authentication protocol, and application-oriented protocol. The research gaps and the challenges faced for secure communication in 5G and IoT networks are listed for further enhancement in the security protocols. We further analysed the research work based on the classification methods, performance metrics, and the year of publication. Our analysis reveals that the most commonly used classification technique is trust-aware routing protocols, and the most frequently used performance metrics is execution time, the execution time of most of the research work lies between 10 ms to 300 ms, and the communication overhead ranges from 1 × 10 5 bits to 5 × 10 5 bits.